1998
DOI: 10.2337/diabetes.47.9.1501
|View full text |Cite
|
Sign up to set email alerts
|

Reversed circadian blood pressure rhythm is associated with occurrences of both fatal and nonfatal vascular events in NIDDM subjects.

Abstract: To assess the significance of reversed circadian blood pressure (BP) rhythms as a predictive factor of vascular events in NIDDM, vital status after an average 4-year follow-up was determined in 325 NIDDM subjects in whom the circadian BP profile had been monitored between 1988 and 1996. Circadian BP rhythm was analyzed by the COSINOR (a compound word for cosine and vector) method, as previously described. After exclusion of 37 dropped-out subjects, 288 were recruited to the further analysis, of which 201 had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 13 publications
4
101
2
3
Order By: Relevance
“…At present, no studies on the long-term predictive value of ambulatory PP for nephropathy progression in patients with type 2 diabetes have been published. Impaired nocturnal BP decline ('non-dipping') is another BP abnormality that has been associated with micro- [1,[10][11][12][13][14][15][16][17] and macrovascular [1,18] complications in type 1 and type 2 diabetic patients. In a recently published 3 year follow-up study in elderly patients with type 2 diabetes [19], patients with a reversed diurnal BP rhythm (nocturnal BP 'risers') had an increased risk of nephropathy progression compared with those who had a normal reduction in BP during the night ('dippers').…”
Section: Introductionmentioning
confidence: 99%
“…At present, no studies on the long-term predictive value of ambulatory PP for nephropathy progression in patients with type 2 diabetes have been published. Impaired nocturnal BP decline ('non-dipping') is another BP abnormality that has been associated with micro- [1,[10][11][12][13][14][15][16][17] and macrovascular [1,18] complications in type 1 and type 2 diabetic patients. In a recently published 3 year follow-up study in elderly patients with type 2 diabetes [19], patients with a reversed diurnal BP rhythm (nocturnal BP 'risers') had an increased risk of nephropathy progression compared with those who had a normal reduction in BP during the night ('dippers').…”
Section: Introductionmentioning
confidence: 99%
“…Even in diabetes, we have shown that ambulatory BP levels more accurately predict future cardiovascular events. 5 An abnormal dipping pattern has been established as a risk factor, 6 and white-coat hypertension and masked hypertension have been shown to be moderate risk factors. 7,8 We showed that BP variability during sleep was a risk factor for cardiovascular disease even after adjusting for BP levels in patients with diabetes.…”
mentioning
confidence: 99%
“…12 At present, it has been proven that the riser pattern is extremely harmful. 6 If this pattern is combined with a sleep disturbance such as short duration of sleep or disordered breathing during sleep, it could have a synergistic impact on the incidence of cardiovascular disease. 13 Chronological therapy in diabetes is also important in patients with diabetes.…”
mentioning
confidence: 99%
“…The loss of nocturnal BP dipping has been considered to be a risk factor for the progression of nephropathy and of prognostic value with respect to target organ damage and cardiovascular morbidity. [1][2][3] Ambulatory BP monitoring allows the acquisition of valuable information not only about the average BP over 24 h (the 24-h BP) but also about the variations in the BP values during the course of the day. Using information from ambulatory BP monitoring, previous studies have found that BP variability is a complex phenomenon that involves both short-and long-lasting changes.…”
Section: T He Accumulated Results Of Clinical Trialsmentioning
confidence: 99%